Bronchogenic cyst of the floor of mouth combined with ankyloglossia: an extremely rare presentation of rare anomaly. Issue 5 (27th May 2021) - Wongprakob, Nuttadon; Sae-Guay, Suthida; Burusapat, Chairat; Wongchansom, Kittisak; Wanichjaroen, Nutthapong
Abstract: Bronchogenic cyst (BC), cyst lined by respiratory epithelium, is uncommon congenital anomaly of bronchial tree. Intraoral BC is extremely rare lesions. Here, we report the unusual presentation of 2-year-old boy with symptomatic cystic lesion at floor of month combined with ankyloglossia. The operation was performed under general anesthesia. Frenotomy was performed. Complete cystic removal was successful with minimal leakage of cyst wall. Sclerosing agent was injected at surgical site to prevent the residual undetected cystic malformation. Pathological examination was demonstrated a unicystic lesion lined by ciliated pseudostratified columnar and cuboidal cells. The final diagnosis was bronchogenic cyst. No postoperative complication was found. The long-term course was uneventful with no signs of recurrence at 1 year. To our best knowledge, a rare example of BC at the floor of mouth combined with ankyloglossia has never been reported.